Dynamics and disorder: on the stability of pyrazinamide polymorphs. Issue 3 (20th June 2022) - Hoser, Anna Agnieszka; Rekis, Toms; Madsen, Anders Østergaard
Abstract : The enantiotropic relationship between the four polymorphs of pyrazinamide is analyzed by means of accurate X‐ray diffraction measurements, normal‐mode refinement and periodic DFT calculations. Abstract : This article focuses on the structure and relative stability of four pyrazinamide polymorphs. New single crystal X‐ray diffraction data collected for all forms at 10 K and 122 K are presented. By combining periodic ab initio DFT calculations with normal‐mode refinement against X‐ray diffraction data, both enthalpic and entropic contributions to the free energy of all polymorphs are calculated. On the basis of the estimated free energies, the stability order of the polymorphs as a function of temperature and the corresponding solid state phase transition temperatures are anticipated. It can be concluded that the α and γ forms have higher vibrational entropy than that of the β and δ forms and therefore they are significantly more stabilized at higher temperatures. Due to the entropy which arises from the disorder in γ form, it overcomes form α and is the most stable form at temperatures above ∼500 K. Our findings are in qualitative agreement with the experimental calorimetry results.